Tidal sedimentation of the Sunderban's Thakuran Basin - Das, Gautam Kumar (Springer, 2016)
This book covers an overview of research on sediment textures, sedimentary structures, sediment composition and bioturbation structures including other aspects of tidal sedimentation. The analytical results for the tidal river sedimentation and essential aspects of relevant field studies along the entire stretch of the Thakuran River are being presented in this book. Filled with interesting results obtained from minutely observations, this book brings together outstanding facts of the tidal river sedimentation and can be considered as a pioneer work on the dynamic estuarine environment of the Sunderbans River. Anyone in academia or NGOs interested in this river basin will find interesting information in this book that will enrich their knowledge on the sedimentation patterns of tidal river systems.
Keywords: River sediments -- Sundarbans (Bangladesh and India); Asia -- Sundarbans.; elektronické knihy; electronic books